Pelatihan : warga peduli aids tingkat kelurahan kota Ternate - Lestari, Tutik; Suma, Fathiyah; Muhlis, Mudini; Rivai, Muhammad (INDRA: Jurnal Pengabdian kepada Masyarakat, 2024)
The community is the front guard in preventing the spread of HIV/AIDS cases. To mobilize community participation in prevention efforts, it is important to provide correct understanding, such as through training. Through the formation of WPA at the sub-district level, this community service aims to empower the community. This WPA functions as a forum for the community to raise awareness that comes from desires or needs without being forced by the community itself, so that the community can contribute significantly to the HIV/AIDS problem in the sub-district environment. The activity was carried out for three days, with a total of 40 participants representing community leaders, health cadres, and the PKK. The methods and forms of activities used are active participation approaches, presentations, and questions and answers. As a result, participants understand their duties and responsibilities in efforts to prevent and control HIV/AIDS by prioritizing community involvement.